The Effect Of Webtoon Application Towards Students Reading Comprehension In Narrative Text - Fajriyah, Enur; Sudirman, Ade; Riandi (Journal of Contemporary Issues in Primary Education, 2025)
This  research  paper  aim  to  investigation  the  effect  of webtoon application towards students’ Reading Comprehension in narrative text. The research paper used the quantitative research design with the characteristics of experimental method  that  is  design  into  two  classes.  They  are  experimental  and  control  class.  The  population  of  this research is class XI of SMKN 1 Malingping, they consists 327 students. The sample of this research is XI MPLB1as an experimental  class  consists  30  students  and  XI  MPLB2  as  a  control  class  consists  of  30 students.  The  total  of sample  is  60  students.  The  instrument is  a  test and  data  of this  research  are  collected  by  giving  pre-test and post-test. The data is analyzed using SPSS version 30.0 program including mean, standard deviation and t-test.  It could be seen from the result of the post-test of experimental and control class. The findings reveal  that  the  data  analysis  and  interpretation  of  the  research,  it  is  clear  there  is  a  significant  effect  of webtoon application towards students’ reading comprehension in narrative text.  It can be seen, the minimum score pre-test experimental calss is 40, maximum is 75,  mean 61,17  andstandard  deviation  8,972. While  the  minimum score  post-test  experimental class is  60, maximum 90, mean 76,17 and standard deviation 7,844. Furthermore, the minimum score of control class is  40,  maximum  75,  mean 60,67 and  standard  deviation 8,066. While  the  minimum  score  post-test  of control  class  is  60,  maximum  85,  mean 71,67 and  standard  deviation 5,921.  The  result  of  t-test obtained sig. value 0.007 ≤ ??? = 0.05. Ha is accepted and Ho is rejected. It can conclude that there is a significant effect of Webtoon application towards students reading comprehension in narrative text.